Ancient deep-sea environmental virome provides insights into the evolution of human pathogenic RNA viruses - Xinyi Zhang; Liquan Huang; Xiaobo Zhang (Resources, Environment and Sustainability)
Pathogenic viruses, especially RNA viruses causing several billions of infections of humans every year in the world, have great threats to human health. The epidemiological survey of pathogenic viruses has been well characterized on the land. However, the origins of the pathogenic viruses are largely unclear. To address this concern, the human pathogenic RNA viruses in the deep sea, the distinctive ecosystem on the earth, was characterized in this study. The mega-scale viromes of the RNA viruses from 157 sediments of the global deep sea identified 153,471 viral operational taxonomic units (vOTUs), representing the largest RNA virus dataset. Only 1.45% of vOTUs were homologous with the known viruses. Of note, 13 human pathogenic viruses belonging to 5 viral families were distributed in the deep sea. Hydrothermal vent was the deep-sea ecosystem rich in potential pathogenic viruses. The sediments containing these RNA viruses were 1,900–24,000 years old, representing that the RNA viruses might be the ancestors of human viruses or the emerging pathogenic viruses in the future. There existed evolutionary relationships among deep-sea coronaviruses of dolphin, gull, bat, and humans, suggesting the transmission of coronaviruses from the deep sea to humans via the intermediate marine animal hosts. Therefore, our findings reveal that the deep sea may be a reservoir of human pathogenic viruses for the first time, opening new areas to track the ecology and evolution of pathogenic viruses as the drivers of disease emergence. Synopsis:: The mega-scale RNA viromes from the ancient deep-sea sediments indicated that the thousands-years-old RNA viruses shared evolutionary relationships to human pathogenic viruses, suggesting that the deep-sea environment was the drivers of viral disease emergence.